Contrasting drivers and trends of ocean acidification in the subarctic Atlantic - Pérez, Fiz F. (2021)
The processes of warming, anthropogenic CO2 (Canth) accumulation, decreasing pHT (increasing [H+]T; concentration in total scale) and calcium carbonate saturation in the subarctic zone of the North Atlantic are unequivocal in the time-series measurements of the Iceland (IS-TS, 1985–2003) and Irminger Sea (IRM-TS, 1983–2013) stations. Both stations show high rates of Canth accumulation with diferent rates of warming, salinifcation and stratifcation linked to regional circulation and dynamics. At the IS-TS, advected and stratifed waters of Arctic origin drive a strong increase in [H+]T, in the surface layer, which is nearly halved in the deep layer (44.7± 3.6 and 25.5 ± 1.0 pmol kg−1 yr−1, respectively). In contrast, the weak stratifcation at the IRM-TS allows warming, salinifcation and Canth uptake to reach the deep layer. The acidifcation trends are even stronger in the deep layer than in the surface layer (44.2± 1.0 pmol kg−1 yr−1 and 32.6 ± 3.4 pmol kg−1 yr−1 of [H+]T, respectively). The driver analysis detects that warming contributes up to 50% to the increase in [H+]T at the IRM-TS but has a small positive efect on calcium carbonate saturation. The Canth increase is the main driver of the observed acidifcation, but it is partially dampened by the northward advection of water with a relatively low natural CO2 content.